2D Oxides for Electronics and Optoelectronics. Issue 8 (12th August 2022) - Hu, Xiaozong; Liu, Kailang; Cai, Yongqing; Zang, Shuang-Quan; Zhai, Tianyou
Abstract : 2D Oxides for Electronics and Optoelectronics 2D oxides can be synthesized in a simple environment and show good stability, which has broad application prospect in electronics and optoelectronics. In article number 2200008, Xiaozong Hu, Shuang‐Quan Zang, Tianyou Zhai, and co‐workers review the advances in the synthesis, basic properties and applications of 2D oxides, highlight the current challenges, future directions and opportunities.